2006
DOI: 10.1590/s0103-507x2006000300004
|View full text |Cite
|
Sign up to set email alerts
|

Anemia e transfusões de concentrados de hemácias em pacientes graves nas UTI brasileiras (pelo FUNDO-AMIB)

Abstract: JUSTIFICATIVA E OBJETIVOS: A anemia é uma condição comum em pacientes graves. A transfusão de hemoderivados aumenta de forma significativa o risco de transmissão de agentes infecciosos e afeta o perfil imunológico. O objetivo deste estudo foi avaliar a incidência de anemia e a prática de transfusão de hemá

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
2
10
0
5
Order By: Relevance
“…(6,17) In the study by Hebert et al, it was seen a prevalence of the male gender, 64%, similar to the observed in the Eastern Europe study. (10,17) In the HNSC ICU the prevalence found was 56.05%, very close to the observed by Chohan et al, 58%, as well as in the Brazilian multicenter study by Lobo et al (5,22) However, the studies did not show a gender influence on pretransfusion parameters, nevertheless the populations differences. (6,10,18) There is an association between the ICU stay and packed red cells transfusion; the longer is the ICU stay, the higher is the transfusion rate.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…(6,17) In the study by Hebert et al, it was seen a prevalence of the male gender, 64%, similar to the observed in the Eastern Europe study. (10,17) In the HNSC ICU the prevalence found was 56.05%, very close to the observed by Chohan et al, 58%, as well as in the Brazilian multicenter study by Lobo et al (5,22) However, the studies did not show a gender influence on pretransfusion parameters, nevertheless the populations differences. (6,10,18) There is an association between the ICU stay and packed red cells transfusion; the longer is the ICU stay, the higher is the transfusion rate.…”
Section: Discussionsupporting
confidence: 71%
“…(10,14,18) These rates are similar to other studies conducted in Brazil, 35%. (21,22) The transfusion rate for the patients in the HNSC study was 19,33%. Significant differences found in the transfusion rates may be explained by the patients population profile within a given hospital, as well as by the recommended treatments and possible complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations